'The Potted Palms is bigger than each of us individually': older musicians playing as community and for community. Issue 1 (21st March 2022) - Joseph, Dawn
Abstract: Participating, learning music and performing are key factors to joining music ensembles. This paper situates itself in Melbourne (Australia) and forms part of my research project Promoting relationships through sound in formal and informal settings where I investigated why members of an instrumental group met to share their music making and practice and how it contributes to their quality of life. I draw on a phenomenological viewpoint from questionnaire and interview data undertaken in May 2018 with the ensemble players. Data were analyzed using Interpretative Phenomenological Analysis that is reported thematically under three broad headings: Music learning for self as a community, wellbeing and spirituality, and sharing music for the community. The findings show that staying active as older adults (50+) contributed to members sense of wellbeing as they continued to engage with music learning and performance. Playing for personal growth contributed positively to members quality of life as a serious leisure activity. Generalization to other instrumental community groups in Australia cannot be made. Further research is required to support the perceived meanings and benefits of planning, preparing, practicing and performing as older musicians.